Gait Analysis of Conventional Total Knee Arthroplasty and Bicruciate Stabilized Total Knee Arthroplasty Using a Triaxial Accelerometer - Takenori Tomite; Hidetomo Saito; Toshiaki Aizawa; Hiroaki Kijima; Naohisa Miyakoshi; Yoichi Shimada (Case Reports in Orthopedics)
One component of conventional total knee arthroplasty is removal of the anterior cruciate ligament, and the knee after total knee arthroplasty has been said to be a knee with anterior cruciate ligament dysfunction. Bicruciate stabilized total knee arthroplasty is believed to reproduce anterior cruciate ligament function in the implant and provide anterior stability. Conventional total knee arthroplasty was performed on the right knee and bicruciate stabilized total knee arthroplasty was performed on the left knee in the same patient, and a triaxial accelerometer was fitted to both knees after surgery. Gait analysis was then performed and is reported here. The subject was a 78-year-old woman who underwent conventional total knee arthroplasty on her right knee and bicruciate stabilized total knee arthroplasty on her left knee. On the femoral side with bicruciate stabilized total knee arthroplasty, compared to conventional total knee arthroplasty, there was little acceleration in the x-axis direction (anteroposterior direction) in the early swing phase. Bicruciate stabilized total knee arthroplasty may be able to replace anterior cruciate ligament function due to the structure of the implant and proper anteroposterior positioning.